Re-examination of how Singaporean Chinese and Malays frame childbearing decisions. - Tay, Pei Si. (2011)
This paper aims to better understand how Singaporean Chinese and Malays talk about fertility differently and similarly. It seeks to find out how they could have drawn on their ethnic culture in the exploration of fertility decisions. Earlier studies, grounded in quantitative methods, have established the relation between culture and reproductive behavior, highlighting ethnicity as an underlying factor for fertility differentials among the various ethnic groups and that differences observed behavioral fertility patterns can be attributed to inherent cultural orientation. However, this paper argues, while cultural differences in values, beliefs and attitudes between Chinese and Malays are accorded to Malay’s consistently higher fertility compared to Chinese; drawing on in depth interview data, I find tertiary educated Chinese and Malays in Singapore have more similar, rather than different ideals in framing childbearing decisions. More importantly, while they might have articulated similar notions, more often than not, how they view children are antagonistic to their practices.